Microbiome and gastrointestinal malignancies. Issue 22 (August 2021) - Sayed, Ibrahim M; Ramadan, Haidi Karam-Allah; El-Mokhtar, Mohamed A; Abdel-Wahid, Lobna
Abstract : Microbiota plays an important role in gut homeostasis and immunity against pathogens. However, the dysbiosis of gut microbiota increases the susceptibility of the host to pathogens leading to the development of several diseases including gastrointestinal (GI) cancers. The gut microbiota mediates GI cancers via several mechanisms such as stimulation of the inflammatory signaling pathways, induction of the host DNA damage, suppression of the host damage repair pathways, secretion of toxic products, and augmentation of uncontrollable host cellular proliferation. Modulation of the gut microbiota by probiotics and/or prebiotic exerts an anticancer effect and could reduce the risk of GI cancers.